Protective effect of hydroxytyrosol and tyrosol metabolites in LPS-induced vascular barrier derangement in vitro - Zodio, Sonia; Serreli, Gabriele; Melis, Maria Paola; Franchi, Benedetta; Boronat, Anna; de la Torre, Rafael; Deiana, Monica (Frontiers in Nutrition, 2024)
The maintenance of endothelial barrier function is essential for vasal homeostasis and prevention of cardiovascular diseases. Among the toxic stimuli involved in the initiation of atherosclerotic lesions, Gram negative lipopolysaccharide (LPS) has been reported to be able to trigger endothelial dysfunction, through the alteration of barrier permeability and inflammatory response.Hydroxytyrosol (HT) and tyrosol (Tyr), the major phenolic compounds of extra virgin olive oil (EVOO), as wells as their circulating sulphated and glucuronidated metabolites have been shown to exert anti-inflammatory effects at endothelial level. In this study we investigated the protective effects of HT and Tyr metabolites on LPS-induced alteration of permeability in Human Umbilical Vein Endothelial Cells (HUVEC) monolayers and examined underlying signaling pathways, focusing on tight junction (TJ) proteins, mitogen-activated protein kinase (MAPK) and NOD-, LRR-and pyrin domain-containing protein 3 (NLRP3) inflammasome activation. Results show that LPS-increased permeability in HUVEC cells was due to the alteration of TJ protein level, following the activation of MAPK and NLRP3. HT and Tyr sulphated and glucuronidated metabolites were able to limit the effects exerted by LPS, acting as signaling molecules with an efficacy comparable to that of their precursors HT and Tyr, adding a further piece to the understanding of their mechanisms of action in vascular protection.